Utilization of Decane, Heptane, Petrol and Hexadecane by Fungi Isolated from Engine Oil Contaminated Soil in Ilorin - D.O. Adetitun; R.D. Sulaiman; M.B. Oguntoye (Journal of Applied Sciences and Environmental Management, 2019)
Fungi with hydrocarbon degrading capabilities were isolated from spent engine oil contaminated soil obtained from five automobile workshops in Ilorin, Nigeria. Preliminary analysis of degradation of the hydrocarbon was performed using Mineral Salts Medium (MSM). The organisms identified include Aspergillus sp., Blastomyces dermatitidis, Cladophialophora bantiana, Mucor circinelloides, Phaeoacremonium parasiticum, Rhizopus arrhizus, Neosartorya fischeri, Cladosporium sp. and Microsporium furrigenum. They were identified based on their morphological and cultural characteristics. Findings from this study showed Aspergillus sp. and Mucor circinelloides were able to degrade hexadecane, heptane, decane and petrol as sole carbon and energy source within 20days. Hydrocarbon utilization rate ranged from 0.020 to 0.284 for heptane, 0.0120 to 0.4965 for decane, 0.079 to 0.340 for hexadecane and 0.023 to 0.268 for petrol. Measurement of optical density and pH was carried to determine hydrocarbon degradation by fungi. The results of this study shows that fungi can play important roles in the effective clean-up of hydrocarbon contaminated soils thereby making them environmentally friendly.